VALIDASI MEDIA PEMBELAJARAN ISPRING SUITE BERBASIS ANDROID PADA KISAH NABI IBRAHIM - Rhomadhoni, Cristina Siti; Sulaikho, Siti (JoEMS (Journal of Education and Management Studies), 2021)
This exploration is development research which plans to foster learning media for aqidah morals using iSpring Suite on the story of the Prophet Ibrahim's Example. The subjects of this research, for grades VII of MTsN 4 Nganjuk, totaling 113 students. The learning device improvement methodology utilized in this investigation is RnD with 4D Thiagarajan model which includes 4 stages. The moral aqidah learning media uses the iSpring Suite after it has been created, approved, mimicked and has gone through a few amendments to deliver good aqidah learning media that is suitable for use. The results of study indicate the validation of material, media, language, student responses, and the material used is legitimate subsequent to being approved by group of skilled. The kind of information generated is qualitative data, which is assessed the opinions of material skilled with an average percentage of 84.83% is categorized very feasible. media expert assessment with an average percentage of 73% eligible category. assessment of linguists with average percentage of 94% categorized very feasible. using the assessment category's criteria to establish the product's quality. The study's findings were based on Meanwhile, the average percentage response of class VII students at MTsN 4 Nganjuk 84.21% is categorized very feasible. Keyword : iSpring Suite, learning media, moral beliefs. ABSTRACT Penelitian ini adalah penelitian pengembangan (Research And Development) bertujuan untuk mengembangkan media pembelajaran iSpring Suite pada kisah teladan Nabi Ibrahim. Subjek penelitian adalah siswa kelas VII A, B dan C pada MTsN 4 Nganjuk yang berjumlah 113 siswa. Jenis penelitian adalah RnD dengan model 4D Thiagarajan Thiagarajang yang mencakup 4 fase. Media pembelajaran aqidah akhlak memanfaatkan iSpring Suite setelah dibuat, disetujui dan direproduksi serta telah melalui beberapa modifikasi untuk menghadirkan media pembelajaran aqidah akhlak yang layak untuk digunakan. Pengumpulan data menggunakan observasi, interview, dan angket. Angket validasi dinilai oleh ahli materi, ahli media, dan ahli bahasa. Penilaian tersebut menggunakan skala Likert dengan ketentuan seperti sangat layak, layak, cukup layak, dan kurang layak. Hasil penilaian dari validasi ahli materi adalah 84,83% dengan kategori yang sangat layak, penilaian validasi dari ahli media adalah 73% dengan kategori layak, dan penilian validasi dari ahli bahasa adalah 94% dengan kategori sangat layak.